1984
DOI: 10.1104/pp.75.2.387
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate Orthophosphate Dikinase of C3 Seeds and Leaves as Compared to the Enzyme from Maize

Abstract: Pyruvate orthophosphate dikinase (PPDK) was found in varis immature seeds of C3 planRts (wheat, pea, green bean, plm, ad castor bean) in some C3 eaves (tobacco, spinach, sunflower, an wheat and in C (maize) kernels. The Protein Blot. PPDK was isolated from maize and purified as previously described (29). Antiserum to PPDK was prepared by injecting New eland white rabbits with 150 pg of the purified enzyme and Freund's complete adjuvant, followed after 26 d by a booster containing the same amount of enzyme a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
61
1

Year Published

1984
1984
2013
2013

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 22 publications
2
61
1
Order By: Relevance
“…A PEPC mediated CO 2 -fixation is known to be part of the metabolic response of plants during phosphorous deficiency, which also affects the energy-metabolism (Theodorou and Plaxton, 1993). Cytosolic PPDK has also been proposed to be involved in amino acid interconversions in seeds (Aoyagi and Bassham, 1984) and the recycling of coenzymes, which could be linked to the accumulation of proline in rice roots during low-oxygen stress (Bertani and Reggiani, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…A PEPC mediated CO 2 -fixation is known to be part of the metabolic response of plants during phosphorous deficiency, which also affects the energy-metabolism (Theodorou and Plaxton, 1993). Cytosolic PPDK has also been proposed to be involved in amino acid interconversions in seeds (Aoyagi and Bassham, 1984) and the recycling of coenzymes, which could be linked to the accumulation of proline in rice roots during low-oxygen stress (Bertani and Reggiani, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The first relates to differences in stainability between polypeptides which vary significantly in structure. Although there is biochemical evidence suggesting that isoforms of the enzymes examined here are different in C3, C4, and C3-C4 plants, there is also evidence indicating that considerable structural integrity has been maintained throughout their divergence (2,14). As a result, differences stained nitrocellulose filter after transfer of gel as in A loaded with 75 sg protein/lane.…”
Section: (4) B Ponceaumentioning
confidence: 99%
“…In C4 leaves, PPDK2 is found in the chloroplasts of the mesophyll cells (8). PPDK is found also in seeds (1,12) and leaves (1) of wheat and in some other C3 plant tissues (for references, see 2). The role of PPDK in C3 leaf tissues is not clearly known, although it has been suggested that it might be involved in the control of stomatal opening (16).…”
mentioning
confidence: 99%
“…The role of PPDK in C3 leaf tissues is not clearly known, although it has been suggested that it might be involved in the control of stomatal opening (16). The occurrence of PPDK in developing wheat seeds does not correlate quantitatively with photosynthetic enzymes (2), and it was suggested that one role of the enzyme might be in the conversion of C3 amino acids, especially alanine, to C4 and C5 amino acids.…”
mentioning
confidence: 99%
See 1 more Smart Citation